Retrospective analysis of 56 soft tissue defects treated with one‐stage reconstruction using dermal skin substitutes. (30th May 2016) - Gümbel, Denis; Ackerl, Martin; Napp, Matthias; Daeschlein, Georg; Spranger, Nikolai; Stope, Matthias B.; Ekkernkamp, Axel; Matthes, Gerrit
Summary: Background: The closure of wounds associated with soft tissue defects is surgically challenging, frequently requiring extensive plastic surgery and free flaps. The combination of dermal skin substitutes and split‐thickness skin grafting is an innovative method used to cover such wounds. We incorporated this technique into the standard therapeutic armamentarium for complex injuries to the extremities. Clinical results of 56 patients thus treated are presented. Patients and methods: In 44 (78.6 %) cases, the method described was used for defects on the lower extremities, including seven (12.5 %) individuals undergoing amputation stump coverage. Twelve (21.4 %) defects were located on the upper extremities. In two (3.6 %) cases, Matriderm ® matrix was used to protect nerves from adjacent surgical implants. Results: In 41 (73.2 %) patients, the graft healed without any complication. Fifteen (26.8 %) patients displayed impaired wound healing following defect closure and were subsequently managed conservatively. One patient (1.8 %) showed graft failure, leading to revision surgery. None of the patients required extensive plastic surgery. Conclusions: In cases where plastic surgery is unavailable or undesirable, the use of dermal skin substitutes in combination with split‐thickness skin grafting represents a promising alternative for covering wounds associated with soft tissue defects.